Ultrafast time-resolved X-ray diffraction - Sokolowski-Tinten, K; Blome, C; Blums, J; Cavalleri, A; Dietrich, C; Tarasevitch, A; von der Linde, D (2002)
Femtosecond laser-generated plasmas emit ultrashort X-ray pulses in the multi-keV range, which allow the extension of X-ray spectroscopy into the ultrafast time-domain. We report here on the generation of such short X-ray pulses and their application for time-resolved diffraction as a means to directly study ultrafast structural dynamics in laser-excited solids.